UJI AKURASI ARAH KIBLAT MASJID AL-MUJAHIDIN (MASJID TUA WATAMPONE) MENGGUNAKAN QIBLAT TRACKER, TONGKAT ISTIWA’ DAN GOOGLE EARTH: UJI AKURASI ARAH KIBLAT MASJID AL-MUJAHIDIN (MASJID TUA WATAMPONE) MENGGUNAKAN QIBLAT TRACKER, TONGKAT ISTIWA’ DAN GOOGLE EARTH - andi mola waliada patodongi; Muh Rasywan Syarif; Zulhas’ari (HISABUNA: Jurnal Ilmu Falak, 2022)
Facing the Qibla is one of the requirements for the validity of prayer, the determination and accurate measurement of the Qibla direction is closely related to the method or instrument used. Along with the times, the instruments used in determining and measuring the Qibla direction also experienced developments from the traditional ones to the most modern tools. This study aims to find out how the community determines the Qibla direction of the Al-Mujahidin mosque and how the accuracy of the Qibla direction of the Al-Mujahidin mosque after measurements are made using these instruments. The type of research used is field research (field research) which is descriptive qualitative, this research uses a normative syar'i and sociological approach, the data sources in this study are primary data and secondary data. data processing and data analysis techniques in the form of: data reduction, data presentation, inference and verification and final conclusion. The results of this study are: the method of measuring the Qibla direction used by the people of the Kingdom of Bone in determining the Qibla direction of the Al-Mujahidin mosque is the shadow of the Sun. The results of measuring the Qibla direction of the Al-Mujahidin mosque which have been carried out using the Qibla Tracker are off 17º, using a special stick deviated 16º, and using Google Earth are off 14º. The implication of this research is that it is hoped that the Bone Regency government, especially the Ministry of Religion, will re-verify the Qibla direction of the Al-Mujahidin Mosque so that the deviations that occur can be corrected. It is hoped that the Bone Regency government will disseminate information about the accuracy of the Qibla direction because of the differences in the results of measuring the Qibla direction of the old mosque with the new research instrument.